Pathophysiological Mechanisms of Endogenous FVIII Release following Strenuous Exercise in Non-severe Haemophilia: A Review - Venema, C.L.; Schutgens, R.E.G.; Fischer, K. (Thrombosis and Haemostasis, 2017)
Introduction Non-severe haemophilia A is characterized by coagulation Factor VIII activity (FVIII:C) levels of 1 to 40 IU/dL. It has been reported that strenuous exercise increases the plasma FVIII:C in haemophilia A patients. This review highlights current knowledge about the pathophysiological mechanisms of endogenous FVIII release following strenuous exercise.Methods A literature search was performed to include relevant studies with data on pathophysiological mechanisms of FVIII release following strenuous exercise in haemophilia.Results The source of the released FVIII is most likely endothelial cells (ECs) from different vascular beds. ECs from human lung, lymph, heart, intestine, skin and pulmonary artery can release and even produce FVIII in response to activation by epinephrine. Ex vivo evidence suggests that FVIII is co-stored with von Willebrand factor in Weibel–Palade bodies in some forms of non-severe haemophilia. The β-adrenergic receptor pathway is involved in increased FVIII levels following strenuous exercise.Conclusion The current available ex vivo and in vivo evidence suggests that endogenous FVIII is released by ECs from different vascular beds in response to epinephrine following strenuous exercise in patients with non-severe haemophilia.
Keywords: epinephrine; exercise; FVIII; haemophilia; endothelial cells